Patterns of cultural consumption and social stratification in Athens: some general remarks on the Greek case - Εμμανουήλ, Δημήτρης (The Greek Review of Social Research, 2016)
The paper reviews the results of a survey of cultural consumption in public venues in Athens in 2013 in the fields of cinema, music and the performing arts - dance and theater. It attempts a synthesis of the findings across all three fields with a view of evaluating the validity of alternative schemata relating cultural consumption to social stratification such as Bourdieu's homology and Peterson's cultural omnivore thesis. While the omnivore phenomenon is limited in this particular case, Bourdieu's hierarchical schema also applies partially in that, alongside adherents of "highbrow" culture substantial segments of upper strata adopt an antithetical "popular" culture. The paper examines this "schism" in the light of a number of views on the nature of "popular" culture and on Greek developments in consumption and cultural politics.